Experimental study of the kinetics and shrinkage of ginger in convective drying (Zingiber officinale Roscoe) - Rivas, Julio; Picado, Apolinar; Martínez, Joaquín; Espinosa, Rodolfo (Nexo Revista Científica, 2023)
In this work, the drying kinetics of ginger (Zingiber officinale Roscoe) was studied considering the shrinkage effect. The experimental data were obtained using three different temperatures (40, 60, and 80 °C). For the determination of shrinkage, two cutting orientations were employed. The volumetric and thickness shrinkage was evaluated by direct measurement. The shrinkage showed two periods during drying and had a considerable effect on the drying rate. An equation that relates the changes in the drying area as a function of the moisture content was determined. During drying, ginger showed only a falling rate period and exhibited a characteristic drying curve.